Chloride migration and long-term natural carbonation on concretes with calcined clays: A study of calcined clays in Argentina - Gisela Cordoba; Ricarda Sposito; Mathias Köberl; Silvina Zito; Nancy Beuntner; Alejandra Tironi; Karl-Christian Thienel; Edgardo F. Irassar (Case Studies in Construction Materials, 2022)
The use of calcined clays as supplementary cementitious materials is one of the strategies to reduce the CO2 emissions from cement and concrete industry as they provide good mechanical and durable properties after proper calcination and grinding. In Argentina, calcined common brick clays have a significant relevance due to their proximity to the largest Portland cement plants. The aim of this study is to analyze the resistance to chloride ingress and natural carbonation up to 36 months of concretes using calcined common brick clay and calcined low-grade kaolinitic clay. The latter exhibits a much lower chloride migration coefficient than the Portland cement concrete from 28 days on, while the calcined common brick clay requires a 90 days curing to obtain lower chloride ingress. Although the blended concretes exhibit greater carbonation depths than the reference after 36 months, it is lower than the given threshold of 10 mm. Hence, durable concretes with calcined clay can be obtained if they are properly cured.